Canadian Consensus Guidelines for the Optimal Use of Etravirine in the Treatment of HIV-Infected Adults - Marianne Harris; Jonathan B Angel; Jean-Guy Baril; Anita Rachlis; Benoit Trottier (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND AND OBJECTIVES: A group of five Canadian physicians with significant experience in HIV management was convened. Their goal was to develop guidance specifically for Canadian HIV-treating physicians on the appropriate use of etravirine (TMC125, Intelence, Tibotec BVBA, Belgium) in adult HIV-infected patients.